Securitisation in China - Characteristics and Difficulties - Wan, Jianzhi (2006)
The characteristics of securitisation have made it popular in recent years, and there is an increasing demand of such financial instrument in Asia. In 2005, three securitisation deals have been put forward in China as signals of both new financial instrument as well as a potential solution to the current Non-Performing Loan problem existed in the Chinese banking industry. This paper will review the current securitisation process in China based on analyzing those three securitisation issuances, namely China United Telecommunication, China Development Bank and China Construction Bank, and compare such process with UK and US to discuss the unique characteristics of securitisation in China, as well as the benefits of Chinese securitisation to the participants involved. In addition, even if the securitisation represents a step forward in the current financial reform, there are still risks & obstacles faced. This paper will evaluate the current difficulties faced and suggest possible solutions accordingly.